2021
DOI: 10.4143/crt.2020.516
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of Predictive Value of Tumor Regression Grades according to Mandard and Becker in Locally Advanced Gastric Adenocarcinoma

Abstract: Tumor regression grade (TRG) has been widely used in gastrointestinal carcinoma to assess pathological responses to neoadjuvant chemotherapy (NCT). There are various standards without a consensus, and it is still unclear which kind of system has better predictive value. This study aims to investigate and compare the predictive ability of the Mandard and Becker TRGs in patients with locally advanced gastric cancer. Materials and Methods A total of 290 patients with locally advanced gastric adenocarcinoma who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…This conclusion is similar to other studies. In other studies, TRG was found to be associated with ypT stage [14,15,21], ypN stage [22,23], histological type [16], Lauren classification [17], differentiation grade [15,23], lymphovascular invasion [21,23] and nervous invasion [24]. Nevertheless, these characteristics after treatment could not be used as a predictor to TRG because these factors and TRG are all obtained at the stage of pathological evaluation.…”
Section: Discussionmentioning
confidence: 95%
“…This conclusion is similar to other studies. In other studies, TRG was found to be associated with ypT stage [14,15,21], ypN stage [22,23], histological type [16], Lauren classification [17], differentiation grade [15,23], lymphovascular invasion [21,23] and nervous invasion [24]. Nevertheless, these characteristics after treatment could not be used as a predictor to TRG because these factors and TRG are all obtained at the stage of pathological evaluation.…”
Section: Discussionmentioning
confidence: 95%
“…The c-index comparison suggested that the four-tier Becker system had the best predictive value for GC patients. Because of their relatively wide measuring distance, four-tier systems based on residual percentages also mean a lower workload, easier understanding of protocols, and less inter-observer disagreement propagation[ 4 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another problem is the different cut-off values of the classification systems, which lead to contradictory findings on which classification best predicts patient survival [55][56][57][58]. This is further aggravated by profound intra-and interobserver variability due to subjective eyeballing in tumor regression evaluation [59].…”
Section: Neoadjuvant Chemotherapy Inhibits Rapidly Proliferating Tumo...mentioning
confidence: 99%